Cherchez la femme: John Keats and Mrs Jones - Bate, A (Times Newspapers Ltd, 2021)
Keats and Mrs Jones had a thing going on. They had a feeling that it was wrong, so they kept very quiet about it. Keats never mentioned her name in writing and only referred to her in two letters to George and Georgiana, his brother and sister-in-law in America. Her identity has always remained a puzzle, leading some biographers to frustration and others to outlandish speculation.